Islamic Education Learning Process in Evaluation Curriculum: The Minister of Religion Decree No.183 and 184 of 2019 - Misbakhus Surur; Muhamad Khoirur Roziqin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The Islamic religious education learning process in the madrasa, is certainly not out of the way to use the Islamic religious education curriculum asa means to achieve education goals. Country 1 jombang madrasa has instituted a kma no. 183 and 184 curriculum in 2019. The researchers' objective in evaluating the curriculum will be to focus on the efforts of the principal, supporters and inhibitors of implementing the kma curriculum no. 183 and 184 year 2019. As for the stages in the execution process, starting from the presence of researchers to the location, looking directly for data sources, interviews, observation and documentation as data gathering step, then analyzing the data to see how far the process of administering it to the Islamic education learning process in implementing the KMA no. 183 and 184 year 2019 curriculum at the Jombang 1 Islamic High School. Based on research conducted by Jombang 1 Islamic High School has applied the kma curriculum no.183 and 184 year 2019. Facilities and policies are also employed as a principal effort to support implementing this curriculum. There are no constraints in the implementation of this curriculum because the kma no.183 and no.184 years 2019 curriculum is an improvement of the previous curriculum, but there are also obstacles to implement because of circumstances which cannot be imposed on direct delivery of material